Применение моделей корпоративной социальной ответственности в Украине - Штернов, А.А.; Яковенко, А.Т. (Культура народов Причерноморья, 2013)
Разобрано состояние социальной ответственности в Украине и применение различных
национальных моделей корпоративной социальной ответственности (КСО) в современных украинских
реалиях. Выделены международные методы КСО, которые могут улучшить состояние социальной
ответственности в Украине. Показано применение методов КСО на примере предприятия ПАО «Завод
«Фиолент».
Ключевые слова: корпоративная социальная ответственность, КСО, модели КСО, применение моделей
КСО Розібраний стан соціальної відповідальності в Україні й застосування різних національних
моделей корпоративної соціальної відповідальності (КСВ) в сучасних українських реаліях. Виділені
міжнародні методи КСВ, котрі можуть покращити стан соціальної відповідальності в Україні.
Показано вживання методів КСВ на прикладі підприємства ПАТ «Завод «Фіолент».
Ключові слова: корпоративна соціальна відповідальність, КСВ, моделі КСВ, застосування моделей КСВ It is sorted condition of corporate social responsibility (CSR) in Ukraine in this article. There is
given definition of term CSR. It on the basis of dynamics of the IISS index is recognized unsatisfactory and much
lagging behind world level. There is actual to Ukraine for the purpose of final overcoming of consequences of an
economic crisis use the best international practices in the social sphere. Recommendations were made
improvement as a whole in Ukraine on the basis of leading world models CSR (European, American, Asian
(Japanese), BRICS countries (Brazil, Russia, India, China, South Africa)). There was briefly characterized the
condition of leading enterprise of the Crimea and Ukraine public company «plant «Fiolent». Its social policy,
its positive results and concrete recommendations about improvement of social indicators at the expense of use
of the best world practices, on the example of the considered enterprise is considered: active involvement of
business partner, stakeholders to social programs; the interaction organization between plant and higher
education institutions of the Crimea; cultural development of social responsibility among employees of plant;
carrying out regular monitoring of level of social responsibility and social well-being of the personnel at the
enterprise; introduction of modern forms of the non-financial reporting.
Keywords: corporate social responsibility, CSR, models of corporate social responsibility, application models
CSR